2022
DOI: 10.3390/microorganisms10061106
|View full text |Cite
|
Sign up to set email alerts
|

The Pork Meat or the Environment of the Production Facility? The Effect of Individual Technological Steps on the Bacterial Contamination in Cooked Hams

Abstract: The aim of this study was to analyse the influence of the contamination level of fresh meat on the bacterial population in raw material before cooking and on the microbiota of cooked hams following heat treatment. The effect of incubation temperatures of 6.5 and 15 °C on the results obtained was also evaluated during the bacteriological investigation. The total viable count (TVC), the number of Enterobacteriaceae and lactic acid bacteria (LAB) were determined in the samples. LAB were isolated from 13 samples o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Moreover, previous studies also reported rapid LAB growth from initially low LAB levels in freshly packed cooked ham [ 5 , 30 , 33 ]. The intrinsic characteristics of cooked ham, such as water activity, sugar-enriched preparations, and the presence of sodium chloride and sodium nitrite, provided a selective advantage for the growth of strict and facultative anaerobic LAB [ 7 , 8 , 12 , 30 ]. The observation of a plateau in LAB growth when the limit of 7.4 log10 CFU/g was exceeded could be attributed to acid production and nutrient depletion, as previously reported when LAB counts reached 8.0 or 9.0 log 10 CFU/g [ 5 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, previous studies also reported rapid LAB growth from initially low LAB levels in freshly packed cooked ham [ 5 , 30 , 33 ]. The intrinsic characteristics of cooked ham, such as water activity, sugar-enriched preparations, and the presence of sodium chloride and sodium nitrite, provided a selective advantage for the growth of strict and facultative anaerobic LAB [ 7 , 8 , 12 , 30 ]. The observation of a plateau in LAB growth when the limit of 7.4 log10 CFU/g was exceeded could be attributed to acid production and nutrient depletion, as previously reported when LAB counts reached 8.0 or 9.0 log 10 CFU/g [ 5 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…gasicomitatum , L. curvatus , C. divergens , which are known to form slime and produce acidic or buttery off-flavors [ 10 ]. Both species were identified as part of a raw meat psychrotrophic microbiota identified in meat during the tumbling process, following their isolation in cooked ham [ 12 ]. It was surprising to observe the absence of microbial growth during the 20 days of storage of cooked ham lot 6.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations